Performance Analysis of Underwater Wireless Optical Communication with Varying Salinity: Experimental Study - Ayaz , Muhammad; Ammad Uddin , Mohammad (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper exhibits the performance of visual light communication in the underwater environment at different salt concentrations. The output is measured in terms of the signal received power at different link budgets. A series of experiments were conducted to verify the results and concluded that light attenuation increases with an increase in water salinity. Furthermore, we analyzed that salinity also affects data rate and link budget. It is found that water salinity cannot block the communication completely as the maximum possible saturation is 40% which can degrade the system by upto 20% only. Along salinity, we also tested the system performance against turbidity and found that it has a much more significant effect. A slight increase in turbidity may block a more considerable portion of the communication channel. The study can help researchers when developing an underwater communication system using visible light for freshwater or salty water (seawater). As per our observation, visual light communication is feasible for both of these environments as even in the saltiest water, it will work because the maximum concentration of salt and percentage of turbidity will not degrade the system beyond a specific limit.